The Role of Salinity in Hard Clam Aquaculture - Shirley Baker; Elise Hoover; Leslie Sturmer (EDIS)
Circular 1500, a 10-page circular by Shirley Baker, Elise Hoover, and Leslie Sturmer, provides answers to many questions clam growers may have about monitoring and managing for salinity in their leases and nurseries. Includes glossary of terms and references. Published by the UF Department of Fisheries and Aquatic Sciences, January 2007.